2006
DOI: 10.1002/ijc.22021
|View full text |Cite
|
Sign up to set email alerts
|

Food patterns and risk of breast cancer: A factor analysis study in Uruguay

Abstract: To generate broad eating patterns, which could explain more adequately the breast cancer etiology, we conducted an exploratory factor analysis in Montevideo, Uruguay. The study included 442 newly diagnosed and microscopically confirmed cases with breast cancer and 442 hospitalized controls, with non-neoplastic diseases. Factor analysis (principal components) was conducted in the control series, and as a result, 6 factors were extracted. These factors were labeled as traditional, healthy, western, stew, high-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
119
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 40 publications
10
119
1
3
Order By: Relevance
“…Pearson coefficients, instead of ICC, for energy-adjusted values were computed and were higher than our values. In addition, Ronco et al (9) developed a questionnaire for Uruguayan adults where Pearson coefficients were also calculated, with similar results to those tested in the present study. For studies assessing validity, correlation coefficients typically range from 0?5 to 0?7 (30) , and coefficients lower than 0?4 may produce a significant attenuation of the association between exposure and event in epidemiological studies (36) .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Pearson coefficients, instead of ICC, for energy-adjusted values were computed and were higher than our values. In addition, Ronco et al (9) developed a questionnaire for Uruguayan adults where Pearson coefficients were also calculated, with similar results to those tested in the present study. For studies assessing validity, correlation coefficients typically range from 0?5 to 0?7 (30) , and coefficients lower than 0?4 may produce a significant attenuation of the association between exposure and event in epidemiological studies (36) .…”
Section: Discussionsupporting
confidence: 76%
“…In Argentina, Chile and Uruguay, several FFQ were developed to assess dietary intakes in adult populations and some of them have been tested by assessing validity, reproducibility or both (9)(10)(11)(12) . To our knowledge, no validation study of a self-administered FFQ has been conducted on adult populations in the Southern Cone of Latin America.…”
mentioning
confidence: 99%
“…In addition, a 'Western' pattern characterized by high consumption of fried, barbecued and processed meat has been positively associated with breast cancer risk (OR 5 2?16, 95 % CI 1?46, 3?29) in Uruguay (18) . A study among Italian women has found an increased breast cancer risk among women with a 'starch rich' dietary pattern (high in bread, pasta dishes, cakes and desserts; OR 5 1?34 95 % CI 1?10, 1?65) (15) .…”
Section: Discussionmentioning
confidence: 99%
“…It is also infor mative to compare the current findings with previous studies that have examined dietary patterns and risk of breast cancer. With the exception of a case-control study conducted in Uruguay [7], they have generally found little evidence for an association of either a ''prudent'' or ''western'' pattern with breast cancer risk [1][2][3][4][5]. In the Nurses' Health Study, the prudent pattern was inversely associated only with ER-postmenopausal breast cancer [2].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have examined single factors or components of the diet. Only a small number of studies [1][2][3][4][5][6][7] have addressed a broader question of whether overall diet or dietary patterns, rather than individual dietary components, affect breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%